Effect of endothelial responses on sepsis-associated organ dysfunction - Miao Wu; Yan Yan; Xinyu Xie; Jiawei Bai; Chengtai Ma; Xianjin Du; Sihan Zhou; Xiuyuan Hao (Chinese Medical Journal)
Abstract. Sepsis-related organ dysfunction is associated with increased morbidity and mortality. Previous studies have found that the endothelium plays crucial roles in maintaining the vascular permeability during sepsis, as well as in regulating inflammation and thrombosis. During sepsis, endothelial cells may release cytokines, chemokines, and pro-coagulant factors, as well as express adhesion molecules. In general, endothelial responses during sepsis typically inhibit bacterial transmission and coordinate leukocyte recruitment to promote bacterial clearance. However, excessive or prolonged endothelial activation can lead to impaired microcirculation, tissue hypoperfusion, and organ dysfunction. Given the structural and functional heterogeneity of endothelial cells in different organs, there are potential differences in endothelial responses by organ type, and the risk of organ damage may vary accordingly. This article reviews the endothelial response observed in sepsis and its effects on organ function, summarizes current progress in the development of therapeutic interventions targeting the endothelial response, and discusses future research directions to serve as a reference for researchers in the field.